EMERGENCY SERVICE IN DISASTERS - Travasso, Cleiton; Silva Zborowski, Feliccia (Health and Society, 2023)
A disaster is considered to be any event that causes major damage, loss of life and imbalance. They include those occurrences that are the result of natural and man-made phenomena. The literature review was carried out based on articles from the BDENF, LILACS, MEDLINE and SciELO databases, legislation and books by authors who deal with the subject. Their respective summaries were read, seeking aspects related to the theme based on the following descriptors: disaster, nursing, assistance, emergency and tragedy. Therefore, the research raises the need for nurses to plan care in relation to disaster events. This research sought to define criteria for disaster management, nursing care in this event, pointing out the possible difficulties encountered by the professional nurse in the face of the scenario with multiple victims. In the area of nursing, there is little reference to studies on the subject, therefore, it is essential to carry out more studies that explore the subject.